Pengaruh Metode Pembelajaran yang Efektif terhadap Minat Belajar Siswa di Sekolah SMA Negeri 3 Pasuruan - Adinda Zuhria Rakhmah; Sugeng Pradikto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to explore the influence of effective learning methods on students' interest in learning at SMA Negeri 3 Pasuruan. The background of this research is based on Republic of Indonesia Law no. 20 of 2003 concerning the National Education System, which emphasizes the importance of developing students' potential. The quality of graduates is closely related to student learning achievement, one of which is interest in learning. It is hoped that the application of effective learning methods can increase students' interest in learning, while contributing to the development of quality education. In this research, the approach used is quantitative with a correlational design..” The independent variable studied is Effective Learning Methods, with indicators of skills, knowledge and teaching and learning processes. Meanwhile, the dependent variable is Student Interest in Learning, which is measured through indicators of concentration/attention, feelings of joy, and interest in learning.“Research data was collected through questionnaires distributed to teachers and students at SMA Negeri 3 Pasuruan, with a population of 996 students, and using simple random sampling techniques. Data analysis was carried out using descriptive and inferential methods, including validity, reliability and classical assumption tests (normality, linearity, heteroscedasticity), along with simple linear regression analysis, t test (partial), and analysis of the coefficient of determination, using SPSS software. This research is expected to provide insight into how learning methods contribute to increasing students' interest in learning.